2022
DOI: 10.1007/s10072-022-06447-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and management of multiple sclerosis patients during the Omicron era: is there a concern about the MS course in the face of the new variant of COVID-19?

Abstract: Introduction The Omicron variant of COVID-19 is highly transmissible, triggering unprecedented infection rates. The present study aimed to investigate the course of multiple sclerosis (MS) in the Omicron era among Iranian patients with MS. Methods This observational study was designed on MS patients of the national MS registry of Iran through a self-designed online questionnaire. A questionnaire was prepared as a Google Form for MS patients during the Omicron outbreak f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Our result is similar to the CovaXiMS cohort in Italy (which delineated infections during the Omicron and Delta waves) where the Omicron variant was found to increase the risk of infection by about 6 times above that during the Delta variant wave [7]. While the Omicron variant appeared to be highly transmissible and infective, it is reassuring that most infections in our cohort were mild (45/47 [95.7%]), in keeping with observations from MS patient cohorts worldwide [7,15]. Indeed, for our patients on anti-CD20s (which have been reported to have an increased risk of severe infections during previous infection waves) [16], 85.7% (12/14) were mild infections.…”
Section: Discussionsupporting
confidence: 90%
“…Our result is similar to the CovaXiMS cohort in Italy (which delineated infections during the Omicron and Delta waves) where the Omicron variant was found to increase the risk of infection by about 6 times above that during the Delta variant wave [7]. While the Omicron variant appeared to be highly transmissible and infective, it is reassuring that most infections in our cohort were mild (45/47 [95.7%]), in keeping with observations from MS patient cohorts worldwide [7,15]. Indeed, for our patients on anti-CD20s (which have been reported to have an increased risk of severe infections during previous infection waves) [16], 85.7% (12/14) were mild infections.…”
Section: Discussionsupporting
confidence: 90%
“…Associations were particularly strong for anti-CD20 treatment and the virus variant, which remained the only significant variables in the multivariate model. The association with neurological disability was not surprising, as several studies have reported higher EDSS scores among patients with severe COVID-19 [2,5,32,33]. Similarly, studies have shown that not only breakthrough infections, but also more severe COVID-19, occur more frequently in anti-CD20 treated MS patients [8,26].…”
Section: Discussionmentioning
confidence: 89%
“…18,19 However, some other committees of the American Academy of Neurology, The Child Neurology Society, and The American Epilepsy Society have noted that EEG can predict further episodes of seizure and recommend considering the EEG as an initial diagnostic tool after the first episode of FS. [20][21][22] Therefore, the role of EEG for patients with FS is not conclusive. However, some demographic and clinical factors investigated do predict abnormal EEG findings in patients with complex FS, including age >3 years and abnormal neurological investigations, as well as conducting EEG within first 7 days after FS.…”
Section: Discussionmentioning
confidence: 99%